The Path Goal Theory of Leader Effectiveness: An Operant Interpretation1 - Mawhinney, Thomas C.; Ford, Jeffrey D. (Academy of Management Review, 1977)
Concepts and terms of the “operant paradigm”, based on the empirical law of effect, are suggested as alternatives to the hypothetical path-goal motivation construct which provides the major premise of the path-goal theory of leadership. Hypotheses in the path-goal theory may be explained by acognitive arguments as well. The resulting interpretation supports the basic propositions comprising the path goal theory without supporting the validity of the motivational model. Advantages and disadvantages of the acognitive alternative premise for a path-goal theory are discussed.